2022
DOI: 10.3389/fphys.2022.875866
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Zebrafish Skeleton in Three Dimensions During Juvenile and Adult Development

Abstract: Zebrafish are a valuable model for normal vertebrate skeletogenesis and the study of myriad bone disorders. Bones grow, ossify and change shape throughout the zebrafish lifetime, and 3D technologies allow us to examine skeletogenic processes in detail through late developmental stages. To facilitate analysis of shape, orientation and tissue density of skeletal elements throughout ontogeny and adulthood, we generated a high-resolution skeletal reference dataset of wild-type zebrafish development. Using microCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Similar to the vertebrae, the zebrafish craniofacial bones did not show a clear decrease in BMD in the old fish. A recent zebrafish study has shown that skeleton density increases with age up to 24 mpf, and this density changes with the body axis, with the highest density observed in the craniofacial skeleton (Nguyen et al, 2022). However, this study did not investigate the detailed density distribution in the head.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the vertebrae, the zebrafish craniofacial bones did not show a clear decrease in BMD in the old fish. A recent zebrafish study has shown that skeleton density increases with age up to 24 mpf, and this density changes with the body axis, with the highest density observed in the craniofacial skeleton (Nguyen et al, 2022). However, this study did not investigate the detailed density distribution in the head.…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid ablation was visually confirmed at 5dpf. Quantification of maxilla position AMIRA (version 6.0.0) was used to visualize µCT scans of adult zebrafish skulls (Blythe, Nguyen et al 2022, Nguyen, Lanni et al 2022. A line was drawn intersecting the parasphenoid at its proximal-and distal-most points to approximate the long-axis of the body.…”
Section: Zebrafish Thyroid Follicle Ablationsmentioning
confidence: 99%
“…These include the facts that osteocytes are not present in all bones, that certain structures such as the skull show greater complexity compared to mammals, and that many different bone and cartilage types with different cellularity and matrix compositions exist in physiological conditions while often only occurring in diseases in vertebrates [30,31]. For a detailed review of the bone development in zebrafish, we would like to refer the reader to several excellent reviews [4,5,9,20,27,[31][32][33][34][35][36]. Here, we will focus on the development of the axial skeleton of teleosts.…”
Section: A Brief Overview Of the Normal Development Of The Axial Skel...mentioning
confidence: 99%